Shape-memory polymer composites selectively triggered by near-infrared light of two certain wavelengths and their applications at macro-/microscale. (18th January 2017) - Fang, Liang; Chen, Shunping; Fang, Tianyu; Fang, Jiaojiao; Lu, Chunhua; Xu, Zhongzi
Abstract: A cost-efficient filler system based on rare earth organic complexes of Yb(TTA)3 Phen and Nd(TTA)3 Phen is reported, showing selective photothermal effect to near infrared (NIR) light of 980 and 808 nm, respectively. The integration of the two fillers into a commercially available SMP of poly[ethylene- ran -(vinyl acetate)] (EVA) respectively provide selective NIR light responsive SMP composites (SMPCs), while their full shape recoveries triggered by NIR light of 980 or 808 nm are correspondingly realized. In addition, the NIR light irradiation periodicity is varied and the results suggests that reducing deformation temperature ( T deform ) of EVA caused the shape recovery at a relatively short exposure time, while long irradiation time must be allowed to trigger the shape deformation at a high T deform . A macroscaled actuator with multi-shaped variation is demonstrated via sequential irradiations of NIR lights of 980 and 808 nm. More interestingly, the shape recovery of a certain pattern on the micropatterned surface consisted of the two composites is triggered first upon one NIR irradiation before the remaining patterned area is stimulated using another NIR wavelength. This work integrates more capabilities into light-induced SMPCs, including multi-shape deformation both at macro and microscale, as well as unique responsive signal, in addition to the known remote and noncontact control.